AQP4 antibodies in neuromyelitis optica: diagnostic and pathogenetic relevance - Jarius, Sven; Wildemann, Brigitte (Nature reviews. Neurology, 2010)
Neuromyelitis optica is a CNS inflammatory disorder that predominantly affects the optic nerves and spinal cord. Jarius and Wildemann review the latest experimental and clinical evidence that supports a direct role for antibodies to aquaporin-4—the most abundant water channel in the brain—in the immunopathogenesis of this condition. The authors also evaluate the range of diagnostic tests that are currently available for the detection of these antibodies.